The impact of classroom interaction on willingness to communicate: The mediating roles of speaking self-efficacy and foreign language enjoyment - Zhiyu Liu; Dawei Sun; Lei Zhang; Xianzhi Wang; Yanchao Yang (PLoS ONE, 2025)
In the realm of second language acquisition, classroom interaction (CI) is pivotal for learners’ language development, and willingness to communicate (WTC) is widely recognized as a key factor in successful language learning. However, previous studies have not fully addressed the impact of CI on WTC, particularly regarding the mediating roles of speaking self-efficacy (SSE) and foreign language enjoyment (FLE). Therefore, this study aims to address these gaps. The research recruited 623 undergraduate students from three universities in China. Data were collected using a self-designed questionnaire that demonstrated strong reliability and validity. Structural equation modeling was employed to test the proposed hypotheses, with bootstrap analysis used to assess the significance of mediation effects. The results revealed that CI had a significant positive direct impact on WTC. Moreover, both SSE and FLE significantly mediated the relationship between CI and WTC. Notably, CI also affected WTC through the chain mediating effect of SSE and FLE. These findings provide empirical support for relevant theories and offer practical implications for language educators, such as fostering interactive classroom environments to boost students’ SSE and FLE, ultimately promoting their WTC in language learning. The limitations and directions for future research were also discussed.